PALACE COUP ON MARCH 11 1801 (HISTORIAN-LEGAL STUDY) - A. Skorobogatov; L. Kuanchaleyeva (Russian Journal of Economics and Law, 2009)
The article is dedicated to historian-legal analysis of the plot and palace coup on March 11 1801, directed on dethronement of the emperor Paul I. The article reveals their essential change from the XVIII century upheaval and similarity of certain elements (the reasons, purpose, participants' composition, organization and implementation methods) with the Decembrists' plot. Basing on the upheaval study the article shows that the murder of Paul I was not prepared beforehand and resulted from several factors, among which on the first place should be given to the unwillingness of Paul I to restrict his authority in any way.